Number Light Media to Stimulate Early Mathematics Abilities in Children in Kindergarten - Mustofa, Muhammad Zaenal; Suarjana, I Made (Universitas Pendidikan Ganesha, 2024)
The ability and understanding of basic mathematics in children, especially aged 5-6 years, is still very low or not good, obstacles to recognizing number symbols, obstacles to recognizing the concept of numbers, and obstacles to pronouncing number symbols. The main objectives of the research is to develop a Number Light media with the aim of stimulating children's knowledge of early mathematics in early childhood aged 5-6 years in Kindergarten to improve initial mathematical abilities in children aged 5-6 years in kindergarten. The research carried out selected a development model, namely ADDIE, and involved four experts, including: one media expert, one material expert, and two practitioners with learning experience. This trial was carried out on a large group consisting of 35 children. Data was collected through questionnaires and analyzed using a combined approach between quantitative and qualitative analysis. The evaluation results show a high level of validity of the Number Light media, with media experts reaching 92%, material experts 89%, practitioners 93%, and large group testing 97%. Based on these results, it is concluded that the development of Number Light media is very useful and suitable for stimulating the early mathematical abilities of children aged 5-6 years in kindergarten.